Relationship Between Sarcopenia and Prognosis in Patient With Concurrent Chemo-Radiation Therapy for Esophageal Cancer - Ma, Dae Won; Cho, Yeona; Jeon, Mi-jin; Kim, Jie-Hyun; Lee, Ik Jae; Youn, Young Hoon; Park, Jae Jun; Jung, Da Hyun; Park, Hyojin; Lee, Chang Geol; Kim, Jun Won; Jeung, Hei Cheul (Frontiers in Oncology, 2019)
Background: Sarcopenia, defined as skeletal muscle loss, has been known as a poor prognosis factor in various malignant diseases The aim of this study is to investigate the effect of sarcopenia on prognosis in patients with esophageal cancer who received concurrent chemo- and radiotherapy (CCRT). Methods: We retrospectively collected clinical data of 287 patients with esophageal cancer who were treated by definite CCRT at Gangnam Severance and Severance hospital from August 2005 to December 2014. The cross-sectional area of muscle at the level of the third lumbar vertebra was measured using pre- and post-CCRT computed tomography images. Sarcopenia was defined as skeletal muscle index <49 cm2/m2 for men and of <31 cm2/m2 for women by Korean-specific cutoffs. Overall survival (OS) and progression free survival (PFS) were analyzed according to sarcopenia. Results: Sarcopenia identified before CCRT did not affect OS and PFS. However, patients with post-CCRT sarcopenia showed shorter OS and PFS than patients without it (median OS: 73 months vs. 28 months; median PFS: 34 months vs. 25 months, respectively). Post-CCRT sarcopenia was an independent prognostic factor of poor OS (hazards ratio: 1.697; 95% confidence interval: 1.036–2.780; P = 0.036). In multivariate analysis, male sex (P = 0.004) and presence of CCRT-related complications, such as esophagitis or general weakness were significantly associated with post-CCRT sarcopenia (P = 0.016). Conclusions: Sarcopenia after CCRT can be a useful predictor for long-term prognosis in patients with esophageal cancer. To control CCRT-related complications may be important to prevent skeletal muscle loss during CCRT.